Gene expression analysis of non-clinical strain of aspergillus fumigatus (LMB-35AA): Does biofilm affect virulence? - Rebaza T.D. (2020)
Aspergillus fumigatus LMB-35Aa, a saprophytic fungus, was used for cellulase production through biofilms cultures. Since biofilms usually favor virulence in clinical strains, the expression of the related genes of the LMB 35-Aa strain was analyzed by qPCR from the biomass of planktonic cultures and biofilms developed on polyester cloth and polystyrene microplates. For this, virulence-related genes reported for the clinical strain Af293 were searched in A. fumigatus LMB 35-Aa genome, and 15 genes were identified including those for the synthesis of cell wall components, hydrophobins, invasins, efflux transporters, mycotoxins and regulators. When compared with planktonic cultures at 37?C, invasin gene calA was upregulated in both types of biofilm and efflux transporter genes mdr4 and atrF were predominantly upregulated in biofilms on polystyrene, while aspHs and ftmA were upregulated only in biofilms formed on polyester. Regarding the transcription regulators, laeA was downregulated in biofilms, and medA did not show a significant change. The effect of temperature was also evaluated by comparing the biofilms grown on polyester at 37 vs. 28?C. Non-significant changes at the expression level were found for most genes evaluated, except for atrF, gliZ and medA, which were significantly downregulated at 37?C. According to these results, virulence appears to depend on the interaction of several factors in addition to biofilms and growth temperature. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.